Polyunsaturated Fatty Acid and Sphingolipid Measurements by Tandem Mass Spectrometry - Aslan, Mutay (Mini-Reviews in Organic Chemistry, 2021)
Linoleic Acid (LA) (omega-6) and Alpha-Linolenic Acid (ALA) (omega-3) are essential fatty acids and give rise to Arachidonic Acid (AA), Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA) that are important in metabolic homeostasis. The omega-6:omega-3 ratio can be a prognostic consideration in cardiovascular and inflammatory diseases. Sphingolipids are bioactive lipids found in cell membranes that play a role in cell growth, differentiation and apoptosis. Electrospray Ionization (ESI) coupled with tandem Mass Spectrometry (MS/MS) is a simple and speedy method to identify and quantify these lipids in various biological matrices. Tandem mass spectrometric analyses can be performed on cell lysates, tissue homogenates and serum samples to measure quantitative changes directly in lipid extracts from these different matrices. The present review summarizes measurement of omega-3 (n-3) and omega-6 (n-6) Polyunsaturated Fatty Acids (PUFAs), their metabolism to eicosanoids and their role in certain disease states. Altered sphingolipid metabolism is also associated with a number of human diseases. Therefore, understanding sphingolipid metabolism is important to comprehend the function of sphingolipids in cellular processes. In this review, we focus on pathways of Ceramide (CER) and Sphingomyelin (SM) synthesis and discuss altered levels reported in disease states. Results of reported studies herein clearly show that PUFAs, SMs and CERs carry out a large number of fundamental functions. They serve as structural elements in cellular membranes, and they work as signaling molecules. Alterations in their amounts of expression occurring in diabetes, obesity, inflammation and ER stress-related conditions lead to dysfunctions contributing to disease pathogenesis.
Keywords: inflammation